Implementation of quantum learning in english language teaching for sports students - Rimma Sianipar; Andromeda Valentino Sinaga; Jonris Tampubolon (Priviet Social Sciences Journal, 2025)
This study provides closer insight into how Quantum Learning may be applied in teaching English to first-semester students in the Universitas Negeri Makassar Physical Education, Health, and Recreation Program. Given its emphasis on active participation, experiential learning, and the creation of a positive learning environment, Quantum Learning is considered a possible means of raising student motivation and participation in language acquisition. The survey consisted of 50 students and utilized a quasi-experimental design to measure the changes in student motivation and participation. Pretest and post-test questionnaires, classroom observations, and follow-up interviews were used to measure the changes. The findings showed a noticeable improvement: student motivation increased by 26.4% and participation increased by 32.0%. Class observations revealed that the students were more active and assertive, especially when discussing in groups, playing games, and conducting experiments. Some students even said that they felt less stressed when communicating in English and that learning was more fun compared to previous classes. But all was not well. One of the most significant challenges was the gap in the level of English proficiency among students. This necessitated teachers to adjust their style so that everyone could maintain pace. Differentiated instructions and adapted support are essential for making learning accessible. Finally, the observations are that Quantum Learning can prove to be a successful method for developing English classes and making them more interactive and student-centric, especially in the sphere of sports education. More research could examine its long-term effects, explore how it can be paired with technology, or examine how it contributes to other language skills, such as writing and listening.